Health promotion in clean and healthy behavior programs in traditional markets - Adnani, Hariza; Subiyanto, AA.; Hanim, Diffah; Sulaeman, Endang Sutisna (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
Health Promotion in Clean and Healthy behavior program is a behavior that can be affected by attitudes, subjective norms, intentions and behaviors. The purpose of this study is to application attitude, subjective norms, intentions, and behavior clean and healthy by using Theory of Reasoned Action. This research type was an analytical observational study with cross-sectional. Research location was in Imogiri traditional market in Bantul Yogyakarta Indonesia. The sampling technique was accidental sampling. Data collection techniques were questionnaire and observation sheet. Data analysis used Amos 24. Attitudes affected the intention; Attitude effect on Behavioral Beliefs; Subjective norms affect Outcome Evaluations; The intention affected the intention of disposing of; The intention affected the intention of utilizing latrines; The intention affected the intention of not smoking in the market; intention affected the intention to wash hands with soap; Clean and healthy life behavior has an effect on non-smoking behavior in the market; Clean and healthy life behavior has an effect on hand washing behavior with soap.